The Effects of Different IBA Concentrations, Light Regimes of in Vitro Rooting and Acclimatization of Invitro Teak (Tectona Grandis L.F) Plantlets - Goh, Maybelline Boon Ling (2003)
The effect of different IBA concentrations, two light regimes of in vitro rooting and acclimatization on in vitro teak ( Tectona grandis L.t) was investigated. The experiments followed a Completely Randomized Design (CRD) involving six concentrations of IBA (0mg/l, 0.5mg/, 1.0mg/l, 2.0mg/l, 3.0mg/l and 5.0mg/l) and two light regimes with 15 replicates each. The in vitro rooting experiments showed that shoots cultures in White medium supplemented with 2.0mg/l and 5 .0mgll IBA produced the best results in terms of mean number of root (6.33=6 and 7.66=8) and mean root length (1l.82mm and 8mm) respectively. In vitro shootlets incubated in the dark exhibited earlier root initiation by five days compared to those incubated in the light. Generally, shoots incubated in the light produced significantly higher mean number of roots (2.3) and mean root length (15.5 mm and 4.5 mm) when supplemented with low concentrations of 0.5mg/l and 1.0mg/l IBA. Conversely when shoots were incubated in the dark, higher mean root length of (14.0mm and 8.8mm) and mean number of root (7.5=8 and 3.3=3 ) were produced when being supplemented with higher concentrations of 2.0mg/l and 3 .0mg/l respectively. Chiefly 2.0mg/l IBA was found to be optimum for rooting of teak as it recorded high mean number of root (6.3=6 and 7.5=8) and mean root length (11.8mm and 1 4.0mm) regardless of light regime. The higher survival percentage of 80% was recorded for plantlet grown in "jiffy-7" but only 40 % survived in the autoclaved soil after one week. However the plantlets failed to continue to survive after the second week due to unforeseen technical error such as a faulty growth chamber. The present result substantiates the requirements of IBA to promote the in vitro rooting of teak shootlets and dark incubation to accelerate rhizogenesis.